Christianity and criminal law - Hill, Mark; Doe, Norman; Helmholz, Richard H.; Witte, John (Law and religion, 2020)
Preface / Lord Judge of Draycote -- Introduction / Mark Hill -- Criminal Law in the Old Testament : Homicide, the Problem of Mens Rea, and God / Brent A. Strawn -- Conflicting Criminal Jurisdictions in Early Christianity / Markus Bockmuehl -- Crime and the Canon Law / R. H. Helmholz -- Retaliation : Christian Reasons for Punishment : An overview / Mathias Schmoeckel -- Christianity and the Liberal Enlightenment Reforms of Criminal Law / Heikki Pihlajamäki -- The Nature of Sin and Crime : Spiritual and Civil Jurisdictions Compared / -- Norman Doe -- Christianity, Mens Rea and the Boundaries of Criminal Liability / David McIlroy -- Christianity, Human Dignity and Due Process / Peter Collier -- Christianity and Crimes Against the State / Nathan S. Chapman -- Christianity and Offences Against the Person / David Etherington -- Law Like Love Like Language : The Christian Uses of Property Crime / -- John F Stinneford -- Crimes against God and the Church / Jeroen Temperman -- Sex Crimes and Christianity / John Witte, Jr -- Attempts, Complicity, Virtue and the Limits of the Law / Richard W. Garnett -- Defences : Justification, Excuse and Provocation / Chloë Kennedy -- Punishment, Forgiveness, and Mercy / Jeffrie Murphy -- Christian Virtue and Pardons / Albert W. Alschuler -- Parole, Risk Assessment of Offenders and Christianity / Sir John Saunders -- Judicial Punishment in Transitional Justice : A Restorative / Daniel Philpott -- The Weight of Judgment / Nathan S. Chapman